2018
DOI: 10.1016/j.ihj.2017.08.011
|View full text |Cite|
|
Sign up to set email alerts
|

Aerobic training and L-arginine supplement attenuates myocardial infarction-induced kidney and liver injury in rats via reduced oxidative stress

Abstract: These results demonstrated that kidney and liver function impaired 14 weeks after MI and aerobic training and L-arginine supplementation synergistically ameliorated kidneys and liver injury in myocardial infarction rats through oxidative stress reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…23 Additionally, studies have shown that exercise reduced serum creatinine and proteinuria in male rats with kidney disease 4,22,26 and reduced serum urea in animals with kidney disease induced by acute myocardial infarction with significant improvement in renal function. 27 The beneficial effects of physical exercise can be attributed to the reduction of hyperglycemia, oxidative stress, and improved bioavailability of nitric oxide in diabetic animals. 20,22,24,41 In this sense, Francescato et al 25 demonstrated that physical preconditioning animals exhibited increased expression of pp-eNOS and eNOS, possibly indicating preserved endothelial function, and increased NO levels in renal tissue, which may have contributed to the reduction of the vasoconstrictor effect and of the inflammatory process in a model of cisplatin-induced acute renal injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23 Additionally, studies have shown that exercise reduced serum creatinine and proteinuria in male rats with kidney disease 4,22,26 and reduced serum urea in animals with kidney disease induced by acute myocardial infarction with significant improvement in renal function. 27 The beneficial effects of physical exercise can be attributed to the reduction of hyperglycemia, oxidative stress, and improved bioavailability of nitric oxide in diabetic animals. 20,22,24,41 In this sense, Francescato et al 25 demonstrated that physical preconditioning animals exhibited increased expression of pp-eNOS and eNOS, possibly indicating preserved endothelial function, and increased NO levels in renal tissue, which may have contributed to the reduction of the vasoconstrictor effect and of the inflammatory process in a model of cisplatin-induced acute renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…61 Exercise also increased eNOS staining in the aorta and reduced neutrophil accumulation and lipid peroxidation in rats with renovascular hypertension. 62 Furthermore, it was demonstrated that aerobic exercise ameliorated kidney 27 and liver 63 dysfunction via reduction of malondialdehyde levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a rat model, aerobic interval exercise protocol was shown to prevent the development of diabetic nephropathy and to affect the metabolism of certain minerals [12]. Moreover, aerobic training in association with L-arginine supplementation also demonstrated to ameliorate kidney and liver damage in myocardial infarction rats, via antioxidant mechanisms [13]. The expression of many cytokines and adipokines associated with metabolic syndrome has also been investigated in obese women, after aerobic training protocol, with positive results [14].…”
Section: Introductionmentioning
confidence: 99%